ANALISIS RESPONS MASYARAKAT TERHADAP INTERNATIONAL TOUR DE BANYUWANGI IJEN PADA TAHUN 2024 DI KABUPATEN BANYUWANGI - Beby Dwi Febriyanti,; Bitsyi Naviri Ismaniar,; Dheanita Sekarini Octanisa,; Khoirunisa, Khoirunisa (Journal of Innovation Research and Knowledge, 2025)
The annual agenda is an integral part of a district's development strategy to attract tourists to visit. Banyuwangi is one of the districts that has a lot of natural, cultural, and man-made potential that can attract tourists to visit. The Banyuwangi Regency Government took advantage of the opportunity by holding an annual agenda to develop tourism, economy, social, and culture, namely by organizing the International Tour de Banyuwangi Ijen (ITdBI). ITdBI is an international competition that is the pride of Banyuwangi residents and is the only road race bicycle race in Indonesia that has been on the official agenda of the World Cycling Federation, UCI (Union Cycliste Internationale) since 2012. Participants in the ITdBI event involved hundreds of athletes, coaches and officials from various countries. The international bicycle racing event "International Tour de Banyuwangi Ijen" (ITdBI) is one of the strategic efforts to promote leading tourist destinations such as Ijen Crater in Banyuwangi. This event not only attracts the attention of bicycle racing fans from home and abroad, but also attracts tourists who want to witness the natural scenery and challenge themselves with extreme racing tracks. In the last five years, this event has shown a positive impact on the increase in the number of tourist visits. Therefore, it is important to examine the public's response to the ITdBI event and the impact of ITdBI on the people of Banyuwangi Regency.